ANIMASI INTERAKTIF PEMBELAJARAN SHALAT MENGGUNAKAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE PADA RA AT-TAUFIQ CIKARANG - Yulihani Yulihani; Siti Masturoh; Agung Fazriansyah; Ahmad Hafidzul Kahfi (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2020)
Abstract— Education is one of the main foundations in shaping one's personality. Learning to pray must be instilled in children from an early age. Prayer is a weapon of believers, a pillar of religion, light in the sky and on earth. Prayers can prevent vile and morbid deeds. Prayers can be judged if they fulfill all the conditions and pillars. The obligation to perform prayer as well as by carrying out other obligations according to the Islamic Shari'ah. This research was conducted using the Adobe Flash application program, using the method of developing Multimedia Development Life Cycle (MDLC) software, the data collection method used in this study were Observation, Interview, and Library methods. From the results of this study, obtained an Interactive Animation of Five Times Prayer Learning using Adobe Flash CS6 as a learning vehicle for students and facilitating RA Ataufiq students at Cikarang in obtaining material information, especially for prayer learning.